Endovascular Treatment for Iatrogenic Right External Iliac Artery Rupture during Transcatheter Chemoembolization of Hepatocellular Carcinoma: A Case Report - Min Jee Kim; Kun Yung Kim; Hong Pil Hwang; Young Min Han (Journal of the Korean Society of Radiology, 2025)
Iatrogenic rupture of the iliac artery during endovascular intervention is a rare but potentially serious complication of vascular interventional procedures that can lead to hemorrhagic shock and death if not diagnosed early and treated promptly. A 51-year-old man underwent transcatheter arterial chemoembolization for hepatocellular carcinoma. During the procedure, the right common iliac artery ruptured, which was identified by extravasation of contrast media on angiography. Urgent balloon tamponade was performed for 20 minutes, followed by contralateral femoral access, and distal aorta ballooning was performed to stabilize the hemodynamics; during ballooning, a balloon-expandable stent graft was deployed from the ipsilateral side. The patient’s vital signs stabilized without complications. This report highlights the importance of prompt recognition and management of iatrogenic vascular injuries during endovascular procedures as well as the efficacy of balloon tamponade, distal aorta ballooning, and stent-graft placement in achieving hemostasis and patient stabilization.